Odpowiedzi

2009-10-11T12:01:56+02:00
A = {x: x € R Λ I2x + 4I ≤ 2}

I2x + 4I ≤ 2
2Ix + 2I ≤ 2
Ix + 2I ≤ 1
x < -2 -- ∨-- x ≥ -2
x ≥ -3 ------ x ≤ -1

x ∈ <-3, -1>

B = {x: x € R Λ I5 - xI ≥ 4}

I5 - xI ≥ 4
x < 5 ----- ∨--- x ≥ 5
5 - x ≥ 4 ------ x - 5 ≥ 4
x ≤ 1 ---------- x ≥ 9

x ∈ (-nieskończoność, 1> u <9, nieskończoność)

A U B = (-nieskończoność, 1> u <9, nieskończoność)
A Π B = <-3, -1>
A\B = pusty
B\A = (-nieskończoność, -3) u (-1, 1> u <9, nieskończoność)
A' = (-nieskończoność, -3) u (-1, nieskończoność)
B' = (1, 9)
2009-10-11T12:14:19+02:00
A = {x: x € R Λ I2x + 4I ≤ 2}

I2x + 4I ≤ 2
-2≤2x+4≤2
-2≤2x+4 i 2x+4≤2
x ≥ -3 ∧ x ≤ -1
mamy
x ∈ <-3, -1>

B = {x: x € R Λ I5 - xI ≥ 4}

I5 - xI ≥ 4
5-x≥4 lub 5-x≤-4
x ≤ 1∨x ≥ 9
mamy
x ∈ (-∞, 1> u <9, ∞)
teraz A=<-3, -1> B=(-∞, 1> u <9, ∞)
wyznaczam
A U B = (-∞, 1> u <9, ∞)
A Π B = <-3, -1>
A\B = zbior pusty
B\A = (-∞, -3) u (-1, 1> u <9, ∞)
A' = (-∞, -3) u (-1, ∞)
B' = (1, 9)